Assessment of genetic diversity and phylogenetic relationships of endangered endemic plant Barbarea integrifolia DC. (Brassicaceae) in Turkey - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2014)
Barbarea integrifolia DC. ( Brassicaceae) is an endangered and endemic species located in Erzincan and Gumushane provinces of Turkey. In total, 27 individuals from 2 natural populations were assessed using the random amplified polymorphic DNA polymerase chain reaction ( RAPD- PCR) method coupled with sequence analysis of the internal transcribed spacer ( ITS1) rDNA region. Genetic accuracy of RAPD- PCR was tested with 25 RAPD primers, and it resulted in 115 clear and reproducible DNA fragments from 13 RAPD primers. Among these, 76 ( 66.1%) fragments were found to be polymorphic. According to the ITS1 analysis of B. integrifolia populations, the plants exhibited a relatively poor genetic diversity. In total, 60 ITS1 nucleotide sequences from the GenBank database with 2 newly identified ITS1 sequences from the Turkish populations were used to construct a maximum- likelihood tree. The lengths of ITS1 sequences of B. integrifolia were found to be 268 bp for population I and 271 bp for population II. ITS1 sequences of B. integrifolia species showed 97% sequence identity. Phylogenetic analysis revealed that Barbarea species were monophyletic and showed high bootstrap values. B. integrifolia had closer relationships with Cardamineae taxa, including Cardamine, Rorippa, and Armoracia. On the contrary, allied genus Nasturtium species were separated from Cardamineae taxa. The genetic information obtained from this study could be used for the development of conservation strategies not only for B. integrifolia but also for rare and endangered plant species.
Keywords: Barbarea integrifolia; ITS1; Brassicaceae; genetic diversity; RAPD; endangered species; MOLECULAR SYSTEMATICS; CRUCIFERAE; NUMBER; GENERA; MATK